Questions & Answers on Practice of Banking: Section A - Esezobor, Emmanuel Amie (Nigeria)
The book covers questions and answer on practice of banking covering banker and customer relationship, types of account holders, banking transactions and determination of banker and customer relationship with teaching sessions.
Includes references.
rua 10/12/14, ijb 13/03/2019
Loans
Keywords: Banks and Banking